Effect of subject restraint and resistance pad placement on isokinetic knee flexor and extensor strength: Implications for testing and rehabilitation - Otten, R.; Whiteley, R.; Mitchell, T. (Sage Publications, 2012)
Background: In clinical practice, several subject restraint and resistance pad placement variations are used when an isokinetic knee flexion/extension test is performed. However, it is unknown if these variations affect the outcome measures. The aims of this study were to determine if these setup variations affect isokinetic outcomes and to establish the smallest detectable difference for these setup variations. Hypothesis: Variation in isokinetic setup affects outcome measures. Study Design: Cross-sectional repeated-measures crossover study. Methods: Ten recreationally active adult men were examined with isokinetic dynamometry on 4 separate days. In the first 3 days, fully strapped and trunk-unstrapped testing was conducted with the resistance pad placed distally on the shin. On days 1 and 3, the unstrapped condition was performed first, followed by the strapped condition. On day 4, the resistance pad was placed proximal on the shin (anterior cruciate ligament testing). Results: There were no within-condition differences for days 1, 2, or 3 for the strapped and unstrapped conditions (P > 0.05). Between-condition comparisons were significant (eg, quadriceps peak torque, P < 0.001; hamstring peak torque, P = 0.043) for the strapped, unstrapped, and proximal resistance pad placement conditions. The strapped condition generally showed the largest torques, and the unstrapped, the least. The smallest detectable differences were relatively large (eg, quadriceps peak torque strapped = 20.6%). The greatest intraclass correlation values were found when strapped.Conclusions: Subject setup significantly influences isokinetic outcome measures at the knee. Since the strapped condition demonstrated the greatest repeatability, it is recommended. The smallest detectable differences were relatively high for all variables and should be considered in the interpretation of the effect size of interventions. Clinical Relevance: Subject setup strapping must be considered when investigating test-retest values or when comparing subjects after isokinetic testing at the knee. The fully strapped condition has the best repeatability and highest torque values.